1,3-Bis(2-chloro-phen-yl)thio-urea: a monoclinic polymorph - Yeo, C.I.; Tiekink, E.R. (International Union of Crystallography, 2011)
The title compound, C(13)H(10)Cl(2)N(2)S, represents a monoclinic polymorph of the previously reported ortho-rhom-bic form [Ramnathan et al. (1996 ▶). Acta Cryst. C52, 134-136]. The mol-ecule is twisted with the dihedral angle between the benzene rings being 55.37 (7)°. The N-H atoms are syn to each other, which contrasts their anti disposition in the ortho-rhom-bic form. In the crystal, mol-ecules assemble into zigzag chains along the c axis via N-H⋯S hydrogen bonds. Chains are connected into layers via C-H⋯Cl inter-actions, and these stack along the a axis.